The Effect of Debt to Asset Ratio, Return on Assets, and Current Ratio on Stock Returns with Earnings per Share as a Mediating Variable in the Property and Real Estate Sector Listed on the Indonesia Stock Exchange - Sandya, Alvaro Danadyaksa; Ryanto, Fuad Ramdhan (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the effect of Debt to Asset Ratio (DAR), Return on Assets (ROA), and Current Ratio (CR) on stock returns with Earnings per Share (EPS) as a mediating variable in property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The study employs a quantitative approach with an associative research design, utilizing secondary data in the form of annual financial statements and stock price data published by the IDX. The research sample was determined using a purposive sampling technique, resulting in 82 companies that met the research criteria. Data analysis was conducted using path analysis with the assistance of SPSS software. The results show that directly, DAR and ROA have a significant negative effect on stock returns, while CR has a significant positive effect on stock returns. In the mediation equation, ROA has a significant positive effect on EPS, CR has a significant negative effect on EPS, while DAR has no significant effect on EPS. In addition, EPS is proven to have a significant negative effect on stock returns, thereby acting as a mediating variable that weakens the relationship between financial variables and stock returns. These findings indicate that in the property and real estate sector, market responses are not always linearly aligned with profitability indicators and earnings per share. This study provides an empirical contribution in clarifying the mechanism of the relationship between financial ratios and stock returns through EPS and serves as a reference for investors and company management in understanding the dynamics of capital market valuation.